Effect of Triazole and Strobilurin fungicides on seed yield and grain quality of winter rapeseed (Brassica napus L.) - Ijaz, Muhammad; Justus Liebig University Giessen (My University, 2012)
Field experiments with rapeseed (Brassica napus L.) were carried out from 2007 to 2010 to clarify the effects of triazole and strobilurin fungicides on seed yield and its components as well as on grain quality of the crop under different growing conditions. The field experiments were conducted at the experimental stations in Giessen (silt clay soil) and Rauischholzhausen (loess soil). Three types of field experiments were carried out: 1. fungicides/growth regulator in combination with two cultivars (two experiments), 2. fungicides in combination with nitrogen (four experiments) and 3. sulphur fertilization in combination with fungicides (three experiments). The used triazole and strobilurin fungicides and the trinexapac growth regulator were applied in different combinations at three different growth stages of winter rapeseed. Morphological and physiological data including seeds/pod, pods/plant, pod length, primary and secondary branches per plant, plant height and leaf area index (LAI) were collected. Incidence of diseases and lodging was assessed. Oil content, fatty acid profile, protein content, content of glucosinolates and free fatty acids as well as peroxide values were analyzed as quality parameters. All collected data were statistically analyzed by statistical package PIAF.Results of the experiments revealed that combined application of triazoles and strobilurins had a marked effect on LAI, largely due to a delay in leaf senescence and thus owing to maintenance of a photosynthetically active area over a longer time. Timings of fungicides had clear effect on plant height and LAI of the plant stand. Plant height was reduced significantly by application of fungicides at BBCH 53 compared with autumn application. Growth regulator Moddus (trinexapac) alone as well as in combination with fungicides increased TGW and improved stem stability by reducing intercalary growth. Morphological parameters (seeds/pod, pods/plant, pod length and primary and secondary branches per plant) of rapeseed were not affected by application of fungicides in all experiments. Combined application of Toprex (paclobutrazole&difenoconazole) and Ortiva (azoxystrobin) increased seed yield due to higher LAI and effectively control of diseases. Caramba (metconazole) and Folicur (tebuconazole) application on its own reduced seed yield relative to their combinations with Ortiva. These triazole fungicides provided disease control to some extent, but suppression of LAI and plant height presumably explained much of the seed yield reduction which they caused.Within seed quality parameters of rapeseed, oil content was enhanced by application of Ortiva in combination with other triazole fungicides by prolonging duration for seed filling. The increase of nitrogen fertilization enhanced protein content and decreased the oil content of the seeds. Significant interaction between fungicides and nitrogen was found regarding oil content. Carax (metconazole&mepiqua chloride) included treatments in combination with lower level of nitrogen increased oil content in comparison with other treatments. Fungicides did not alter protein content significantly in most field experiments. Cultivar NK Fair exhibited significantly higher oil, protein and oleic acid contents in comparison with cv. Elektra. Sulphur application enhanced protein percentage but had no effect on oil content. Application of Moddus at BBCH 53 alone as well as in combination with fungicides somehow reduced glucosinolates in all experiments. Fungicides did not exceed the values of free fatty acids and peroxides at such hazardous limits. Wet weather conditions and severe lodging near to maturity also contributed to influence free fatty acids and peroxides in the oil of rapeseed. The proportion of oleic acid was unaffected, while polyunsaturated fatty acids (linoleic and linolenic acid) were affected significantly by the application of fungicides in most experiments. Oleic acid showed a positive correlation with oil content and it was negatively correlated with polyunsaturated fatty acids. Generally it can be concluded that application of triazole and strobilurin fungicides may have various effects on winter rapeseed physiology by increasing leaf area index and modifying the optimal upright canopy. Plants which are applied with these fungicides are less susceptible to lodging, and characterized by delayed leaf senescence which promoted the light interception of plant stand. Triazole and strobilurin fungicide combinations have the potential to improve several growth parameters which limit the yield of winter rapeseed. The use of fungicides prevented a considerable loss in yield, but had no deleterious effect on oil quality.

In der Zeit von 2007 bis 2010 wurden mehrere Feldversuche mit Winterraps (Brassica napus L.) durchgeführt, um den Einfluss von Triazol- und Strobilurin-Fungiziden auf den Samenertrag und die Ertragskomponenten sowie auf die Qualität der Samen unter unterschiedlichen Wachstumsbedingungen zu klären.Die Feldversuche wurden in den Versuchsstationen Gießen (schluffiger Tonboden) und Rauischholzhausen (Lössboden) mit drei Fragestellungen durchgeführt: 1. Fungizid/Wachstumsregulator in Kombination mit zwei Sorten (zwei Versuche); 2. Fungizide in Kombination mit Stickstoff (vier Versuche) und 3. Schwefeldüngung in Kombination mit Fungiziden (drei Versuche). Die verwendeten Triazol- und Strobilurin-Fungizide sowie der Wachstumsregulator Trinexapac wurden in unterschiedlichen Kombinationen zu jeweils drei verschiedenen Wachstumsstadien des Winterrapses appliziert. Es wurden Daten zu morphologischen und physiologischen Parametern erhoben, darunter Samen/Schote, Schoten/Pflanze, Schotenlänge sowie die Anzahl der primären und sekundären Seitentriebe pro Pflanze, die Pflanzenhöhe und der Blattflächenindex. Darüber hinaus wurden das Auftreten von Krankheiten und Lager evaluiert und die Qualitätsparameter Ölgehalt, Fettsäureprofil, Proteingehalt, Glucosinolatgehalt, der Gehalt an freien Fettsäuren und die Peroxidzahl gemessen. Sämtliche erhobenen Daten wurden mit dem Statistikprogramm PIAF ausgewertet.Die gewonnenen Ergebnisse zeigten, dass eine kombinierte Anwendung von Triazolen und Strobilurinen einen deutlichen Einfluss auf den Blattflächen-Index hat. Dieser Einfluss ist im Wesentlichen auf eine verzögerte Blattseneszenz und somit auf die damit einhergehende Aufrechterhaltung verlängerte Photosynthese-Aktivität der Pflanzen zurückzuführen. Der Zeitpunkt der Fungizidapplikation hatte einen signifikanten Einfluss auf die Pflanzenhöhe und den Blattflächenindex des Pflanzenbestandes. Die Pflanzenhöhe wurde durch die Fungizidapplikation im Stadium BBCH 53, im Vergleich zur Herbstapplikation, signifikant reduziert. Der Wachstumsregulator Moddus (Trinexapac) reduzierte sowohl einzeln als auch in Kombination mit den Fungiziden das interkalare Wachstum der Halme und verbesserte damit die Standfestigkeit sowie das TKG der Pflanzen. Morphologische Merkmale des Rapses wurden durch die Applikation der Fungizide in keinem der Versuche beeinflusst. Die kombinierte Anwendung von Toprex (Paclobutrazol&Difenoconazol) und Ortiva (Azoxystrobin) erhöhte den Samenertrag aufgrund des verbesserten Blattflächenindexes und der geringeren Krankheitsanfälligkeit. Die Anwendung von Caramba (Metconazol) und Folicur (Tebuconazol) allein reduzierte den Samenertrag im Vergleich zu deren Kombination mit Ortiva. Diese Triazolfungizide führten zwar zu einer Verminderung der Krankheiten, reduzierten jedoch den Samenertrag, was vermutlich auf einen niedrigeren Blattflächenindex und eine geringere Anlage von ertragsrelevanten Organen der Pflanze zurückzuführen ist.Die Anwendung von Ortiva hatte in Verbindung mit anderen Triazolfungiziden eine Erhöhung des Ölgehaltes aufgrund der längeren Kornfüllungsphase zur Folge. Die Erhöhung der Stickstoffdüngung führte erwartungsgemäß zu einem höheren Proteingehalt und zu einem geringeren Ölgehalt der Samen. In den durchgeführten Versuchen wurde eine signifikante Wechselwirkung zwischen Fungiziden und Stickstoff-Düngung festgestellt. In den meisten Feldversuchen wurde der Proteingehalt durch die Fungizidapplikation nicht signifikant verändert. Im Vergleich mit Elektra wies die Sorte NK Fair signifikant höhere Gehalte an Öl, Protein und Ölsäure auf. Schwefeldüngung erhöhte den Proteingehalt, hatte jedoch keinen Einfluss auf den Ölgehalt in den Samen. Die Applikation von Moddus bei BBCH 53, einzeln und in Kombination, reduzierte den Gehalt an Glucosinolaten in allen durchgeführten Versuchen. Die Gehalte an freien Fettsäuren und Peroxiden im Öl wurden vor allem durch die feuchte Witterung und durch das Lagern der Rapspflanzen erhöht. Der Anteil an Ölsäure blieb zumeist unverändert, während der Anteil an mehrfach ungesättigten Fettsäuren in den meisten Versuchen beeinflusst wurde. Der Ölsäuregehalt korrelierte positiv mit dem Ölgehalt, während sich eine negative Korrelation mit mehrfach ungesättigten Fettsäuren zeigte.Aus den Ergebnissen lässt sich schließen, dass die physiologische Wirksamkeit von Triazol- und Strobilurin-Fungiziden zum Teil auch unter Feldbedingungen nachgewiesen werden kann. Pflanzen, die mit diesen Fungiziden behandelt wurden, zeigten generell eine geringere Lagerneigung und eine verzögerte Blattseneszenz, wodurch die Lichtinterzeption im Pflanzenbestand verbessert wird. Die kombinierte Anwendung von Triazol- und Strobilurin-Fungiziden kann somit zahlreiche Wachstumsparameter verbessern, die für die Ertragsbildung des Winterrapses von Bedeutung sind.
Keywords: ddc:630